Teacher Cognition and Practice of Educational Equity in English as a Foreign Language Teaching - Chen, Feifei; Abdullah, Rohaya Binti (Frontiers in Psychology, 2022)
Teachers involved in English as a foreign language (EFL) teaching play a significant role in the process of moving toward educational equity. Teacher cognition is very influential in shaping teacher practice and thus affects students’ academic performance. However, although the role of EFL teachers as equity agents has been recognized, few studies have explored EFL teachers in-depth in terms of their cognition and practice. Moreover, no review studies have given sufficient attention to the task of elucidating the interrelations between EFL teachers’ cognition and practices in the context of educational equity. Therefore, to provide a novel perspective and generate fresh insights into this research field, the current study attempts to explain the connotations of these constructs, highlights the interplay between EFL teachers’ equity-oriented cognition and practice, and identifies both experiential and contextual factors that might have an effect throughout the teaching process. Finally, practical implications and directions for teachers, researchers, policy-makers, and social justice leaders who are interested in actualizing education as a means of attaining equity are also discussed.